SUCCESSFUL MANAGEMENT OF HYDRALLANTOIS IN A MID-GESTATION GIR COW- A CASE REPORT - ABARNA, M; PUGAZHARASI, C; NAVANEETHAKRISHNAN, S; ARUNAMAN, C S; SURESHKUMAR, R; ARUNMOZHI, N; JOSEPH, CECILIA; SARATH, T (The Indian Journal of Animal Reproduction, 2020)
A pluriparous Gir cow was presented to the Large Animal Outpatient Medicine Unit of Madras VeterinaryCollege Teaching Hospital with the history of anorexia, distended abdomen and scanty dung for the past one week.On clinical examination, bilateral distension of abdomen was observed. Per-rectal examination revealed severelydistended uterus with prominent fremitus. Sonographic examination revealed presence of fluid filled sacs withintermittently moving foetus, cranial displacement of abdominal organs and severe hepatic congestion. The conditionwas diagnosed as hydrallantois based on per-rectal findings and ultrasound examination. Hence, the pregnancy wasterminated using intramuscular injection of Cloprostenol sodium @ 500μg and Dexamethasone @ 24mg. After 20hours of treatment, the cow had expelled around 80-100 litres of yellowish, serous fluid along with a live 5 months oldmale foetus without any abnormality or congenital deformity which died within an hour and the cow had recoveredimperceptibly.
Keywords: Gir cow; Hydrallantois; Trans-abdominal ultrasonography